A Comparative Study of Cervicography and Histopathology Reports from Colposcopic-Directed Biopsies at a Tertiary Care Hospital in Pathum Thani, Thailand - Kittiniyom, Pitchapong; Promchit, Kanokwan; Khongthon, Nop; Benchahong, Sawanya; Suwannarurk, Komsun (Asian Pacific Journal of Cancer Care, 2026)
Introduction: This study aimed to evaluate the diagnostic performance of cervicography (CG) in detecting cervical intraepithelial neoplasia (CIN) grade 2 or higher (CIN2+) and to compare the diagnostic performance among examiners with different levels of clinical experience. Materials and Methods: We conducted a retrospective descriptive study at Thammasat University Hospital in Pathum Thani, Thailand, from October 2023 to November 2024. Participants included women who underwent colposcopy and colposcopy-directed biopsy. CG images were independently interpreted by a gynecologic oncologist (expert) and two Obstetrics and Gynecology residents (R1, R2), all of whom were blinded to clinical and histopathologic data. The interpretations from the expert, R1, and R2 were compared to the histopathologic reports of cervical biopsy. Results: A total of 160 participants were recruited for the study. The mean age of participants was 42.5 years. High-risk HPV was detected in 96.3% (104/108) of participants. Histopathology confirmed CIN2/3 in 24.4% (39/160) and cancer in 0.6% (1/160) of participants. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for detecting CIN2+ among expert, R1, and R2 were 47.5/45.0/47.5, 95.0/85.8/78.3, 76.0/51.4/42.2, and 84.4/82.4/81.7 percent, respectively. Specificity and PPV were significantly higher for the expert, while sensitivity and NPV were similar across examiners. Conclusion: CG demonstrated acceptable diagnostic performance in detecting CIN2+. While specificity and PPV increased with examiner experience, sensitivity stayed consistent across different training levels.